2022
DOI: 10.1097/rd9.0000000000000055
|View full text |Cite
|
Sign up to set email alerts
|

Identifying miRNA biomarkers of polycystic ovary syndrome through text mining

Abstract: Objective: Polycystic ovary syndrome (PCOS) is an endocrine disorder with diverse clinical manifestations that often occurs in women of childbearing age. However, its molecular pathogenesis remains unclear, and this study aimed to identify miRNA targets in PCOS through text mining and database analysis. Methods: First, three different sets of text mining genes (TMGs) associated with “polycystic ovary syndrome”, “obesity/adiposis”, and “anovulation” keywords were retrieved from the GenCLiP3 database, and over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Hu et al identified IGF1 , VEGFA , and SERPINE1 as targets in glaucoma using text mining [6] . Wang et al identified ovarian steroidogenesis as a potential pathway for PCOS [7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al identified IGF1 , VEGFA , and SERPINE1 as targets in glaucoma using text mining [6] . Wang et al identified ovarian steroidogenesis as a potential pathway for PCOS [7,8] .…”
Section: Introductionmentioning
confidence: 99%